Molecular mapping and validation of quantitative trait loci for content of micronutrients in wheat grain - Chen, Xiangdong; You, Junchao; Dong, Nannan; Wu, Di; Zhao, Die; Yong, Rui; Hu, Wenjing (Frontiers in Plant Science, 2025)
Manganese (Mn), iron (Fe), copper (Cu), zinc (Zn), and selenium (Se) are essential micronutrients for human health. However, the genetic basis for the content of Mn, Fe, Cu, Zn, and Se in wheat grains remains unclear. A recombinant inbred lines (RIL) population derived from Yangmai 4/Yanzhan 1 (YM4/YZ1) with wheat 55K single nucleotide polymorphism (SNP) arrays and micronutrient content of two environments was used to construct a genetic linkage map and dissect the quantitative trait loci (QTL) for the content of Mn, Fe, Cu, Zn, and Se in wheat. A total of 8 QTL were detected and located on chromosomes 1A, 1B, 2D, 4D, 7A, and 7D, respectively. Among them, QFe.yaas-2D and QSe.yaas-2D were co-located on chromosome 2D, while QMn.yaas-4D and QZn.yaas-4D were co-located on chromosome 4D, which were in the dwarfing locus of Rht-D1 region. The positive alleles of QCu.yaas-1A, QMn.yaas-1B, and QZn.yaas-7D were contributed by YZ1 and explained 7.66–19.92% of the phenotypic variances, while the positive alleles of QFe.yaas-2D, QSe.yaas-2D, QMn.yaas-4D, QZn.yaas-4D, and QCu.yaas-7A were contributed by YM4 and explained 5.77–20.11% of the phenotypic variances. The positive alleles of QCu.yaas-1A, QMn.yaas-1B, and QMn/Zn.yaas-4D increased TGW by 3.52%, 3.45%, and 7.51% respectively, while the positive alleles of QFe/Se.yaas-2D decreased TGW by 6.45%. Six SNP markers flanked the target QTL were converted into Kompetitive allele specific PCR (KASP) markers, and their effects were validated in a panel of one hundred and forty-nine wheat advanced lines. Twenty-five advanced lines harboring at least five positive alleles were identified in the validation populations. A total of 60 and 51 high-confidence annotated genes for QFe/Se.yaas-2D and QMn/Zn.yaas-4D were identified using the International Wheat Genome Sequencing Consortium Reference Sequence v2.1 (IWGSC RefSeq v2.1), respectively. Some genes in these two regions were involved in stress tolerance, growth development, Zn synthesis in plants. These results provide the basis for fine-mapping the target QTL of micronutrient content and marker-assisted selection in grain quality breeding programs.